Distance Learning During COVID-19 Pandemic: A Comparison between Schools in Urban dan Rural Area in Bali - Pratiwi, Ni Putu Astiti; Gading, I Ketut (Universitas Pendidikan Ganesha, 2023)
Covid-19 pandemic has posed significant challenges to the education system. Most schools with limited or no experience with online learning and schools with no prepared online learning sources will encounter some challenges. This research analyzes similarities and differences between the difficulties faced by teacher and students for schools in different locations. Schools in rural and urban area of Buleleng were chosen, 2 elementary school, 2 junior high school, and 2 senior high schools. Teacher and students in those schools were observed and interviewed related to their online learning implementation, their difficulties, as well as their ways to cope with the difficulties. In analyzing the qualitative data consists of three steps such as, data reduction, data display and conclusion drawing. The result shows that the difficulties faced were not so much different, between urban and rural school teachers and students. Most of them mention internet connection as the problem. However, their ways to cope with the difficulties are varied. Urban and rural teachers and students have their own way to solve their problems. These differences give insight in order to face difficulties in implementing online learning.